Identifikasi Bakteri Toleran terhadap Logam Berat Pb yang Diisolasi dari Air dan Sedimen di Sungai Porong, Sidoarjo - Nur Rokhmatul Lailiya; Misbakhul Munir; Esti Tyastirin; Eko Teguh Pribadi; Hanik Faizah (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
Porong River is an active river located in the Sidoarjo region, East Java which has been polluted by the Lapindo mudflow containing various chemical compounds, one of which is lead (Pb) heavy metal. Isolation of bacteria in the environment contaminated with Pb allows bacteria that have the potential as bioremediation agents to grow. The purpose of this study was to determine the content of heavy metal Pb and isolate and identify lead (Pb) tolerant bacteria in water and sediment at Porong river, Sidoarjo. Sampling of water and sediment was carried out at 2 sampling points based on the presence of Lapindo mud waste flow. Analysis of the heavy metal content of Pb was carried out using the Atomic Absorption Spectrophotometer (AAS). Bacterial isolation was carried out on NA media containing 10 ppm Pb of heavy metal and incubated for 24 hours at 300C. Bacterial isolates were identified based on the macroscopic and microscopic properties and biochemical tests. The results of the heavy metal content of Pb at sampling point 1 in water was 0.81 ppm, and in sediment was 0.98 ppm while at sampling point 2 in water was 2.93 ppm, and in sediment was 3.88 ppm. The results of bacterial identification obtained as many as 6 bacterial isolates belonging to 3 genera of bacteria including Bacillus, Acinetobacter and Pseudomonas.